O preconceito como obstáculo à educação sexual: reflexões a partir de uma perspectiva ética - Maia, Ari Fernando [UNESP] (My University, 2010)
This paper developed a reflection about problems related to the establishment of ethical principles that guide the sexual education aiming at emancipation. Our theoretical framework is the Critical Theory of Society, in particular texts by T. W. Adorno on training, prejudice and education. It is understood that numerous difficulties are related to the achievement of an emancipatory education, and such difficulties are even greater when it comes to sex education since it is an issue that still raises irrational fears on educators, and is absent from the training they received. Following Adorno, it is understood that the current formation favors the development of subjects inclined to prejudice, and that an emancipatory sexual education involves a critique to the conditions under which such formation occurs and, at the same time, a continuous reflection about the relations between the desires and the social possibilities of their realization.

Este texto desenvolve uma reflexão sobre os problemas relacionados ao estabelecimento de princípios éticos que orientem a realização de uma educação sexual que vise à emancipação. Tem por referencial teórico a Teoria Crítica da Sociedade, em especial textos de T. W. Adorno, sobre formação, preconceito e educação. Entende-se que inúmeras dificuldades estejam relacionadas à realização de uma educação emancipatória, e que essas dificuldades são ainda maiores quando a questão é educação sexual, pois se trata de um tema que ainda suscita temores irracionais nos educadores, e se encontra ausente da formação que eles receberam. Seguindo as reflexões de Adorno, entende-se que a formação atual favorece o desenvolvimento de sujeitos propensos ao preconceito. Uma educação sexual emancipatória implica crítica às condições em que tal formação ocorre e, ao mesmo tempo, uma contínua reflexão sobre as relações entre os desejos e as possibilidades sociais de sua realização.
Keywords: Sexuality; Sex education; Ethics; Bias; Teachers’ training; Critical theory; Sexualidade; Educação sexual; Ética; Preconceito; Formação de professor; Teoria crítica